Clinical investigation of nosocomial infections in adult patients after cardiac surgery. Issue 4 (29th January 2021) - Liu, Zhengqin; Zhang, Xiquan; Zhai, Qian
Abstract : Abstract: Nosocomial infections (NI) are common complications after cardiac surgery. To date, there have been few manuscripts investigating NI in the intensive care unit after cardiac surgery. Our study was designed to investigate the characteristics of the distribution of pathogenic bacteria, antibiotic resistance and risk factors for NI. A total of 1360 patients received standard postoperative care, including antibiotic prophylaxis. Microbiological examinations of sputum, blood, catheter tips and excrement were performed as clinically indicated to isolate pathogens. Thirty potential associated variables were collected and compared between the 2 different groups according to the development of NI using univariate and multivariate analyses. Eighty-nine patients (6.54%) acquired a microbiologically documented NI. There was a significant difference in mortality between the 2 groups with or without postoperative NI (23.60% vs 2.28%, P < .00). A total of 98 pathogens (73.13%) were isolated from sputum, 32 pathogens (23.88%) from blood and only 1 (0.75%) from urine. Three (2.24%) surgical site infections were detected, including 2 superficial surgical site infections and 1 mediastinitis. The most common pathogens were Gram-negative bacteria (78.36%), followed by Gram-positive bacteria (14.93%) and fungi (6.71%). The major pathogenic species had different levels of drug resistance, and most of them exhibited multidrug resistance. Six out of thirty variables were identified as independent risk factors for the development of NI, namely, duration of surgery, low cardiac output syndrome, continuous veno-venous hemofiltration, mechanical ventilation time, reintubation and tracheostomy. We analyzed the characteristics of the distribution of pathogens, antibiotic resistance and risk factors for NI in our center and provided some suggestions for clinical practice. In addition to antibiotic treatment, avoidance of risk factors and aggressive infection control measures may be crucial to stop or prevent outbreaks.